Comparison of two Kampo medicines in a diet‐induced mouse obesity model. Issue 2 (13th May 2015) - Gao, Fengying; Yokoyama, Satoru; Fujimoto, Makoto; Tsuneyama, Koichi; Saiki, Ikuo; Shimada, Yutaka; Hayakawa, Yoshihiro
ABSTRACT: Aim: Boiogito (BOT) and bofutsushosan (BTS) are major traditional Kampo medicines that have been widely used for obesity in Japan. In this study, we used a high‐fat diet‐induced obesity (DIO) mouse model to conduct a comparative study of the therapeutic efficacy of BOT and BTS in obesity. Methods: C57BL/6J mice were fed a high‐fat diet for 10 weeks in order to generate the DIO mouse model and were treated with Kampo medicines for 12 weeks. Bodyweight and food intake were monitored weekly and blood and tissue samples were collected. Results: While neither BOT nor BTS had any significant impact on body composition in the DIO mice, serum leptin was significantly decreased in both BOT‐ and BTS‐treated DIO mice. In contrast to blood leptin, BOT suppressed, whereas BTS increased, blood insulin in the DIO mice. In addition to these serum obesity markers, BOT reduced liver triglyceride and total cholesterol content, as well as steatosis. Importantly, the mRNA expression of molecules associated with lipid metabolism was reduced in the DIO mice treated with BOT, whereas BTS instead reduced liver mRNA expression of tumor necrosis factor‐α. Both BOT and BTS inhibited adipocyte maturation, as seen in the inhibition of adipocyte enlargement in the white adipose tissue of DIO mice. Conclusion: BOT and BTS have different therapeutic benefits in obesity due to their modulation of lipid metabolism and of anti‐inflammatory effects, respectively.